3D-visualization of amyloid-β oligomer interactions with lipid membranes by cryo-electron tomography. Issue 20 (7th April 2021) - Tian, Yao; Liang, Ruina; Kumar, Amit; Szwedziak, Piotr; Viles, John H.
Abstract : Cryo-electron tomography 3D imaging of amyloid-β oligomers carpeting the surface of lipid bilayers in near native conditions. Abstract : Amyloid-β (Aβ) assemblies have been shown to bind to lipid bilayers. This can disrupt membrane integrity and cause a loss of cellular homeostasis, that triggers a cascade of events leading to Alzheimer's disease. However, molecular mechanisms of Aβ cytotoxicity and how the different assembly forms interact with the membrane remain enigmatic. Here we use cryo-electron tomography (cryoET) to obtain three-dimensional nano-scale images of various Aβ assembly types and their interaction with liposomes. Aβ oligomers and curvilinear protofibrils bind extensively to the lipid vesicles, inserting and carpeting the upper-leaflet of the bilayer. Aβ oligomers concentrate at the interface of vesicles and form a network of Aβ-linked liposomes, while crucially, monomeric and fibrillar Aβ have relatively little impact on the membrane. Changes to lipid membrane composition highlight a significant role for GM1-ganglioside in promoting Aβ-membrane interactions. The different effects of Aβ assembly forms observed align with the highlighted cytotoxicity reported for Aβ oligomers. The wide-scale incorporation of Aβ oligomers and curvilinear protofibrils into the lipid bilayer suggests a mechanism by which membrane integrity is lost.